Safety and effectiveness of thermal radiofrequency applied to the musculocutaneous nerve for patients with spasticity - Otero-Villaverde, Sergio; Formigo-Couceiro, Jacobo; Martin-Mourelle, Rosa; Montoto-Marques, Antonio (Frontiers in Neurology, 2024)
OBJECTIVE: Evaluate safety and effectiveness of thermal radiofrequency in the musculocutaneous nerve in patients with focal elbow flexor spasticity. DESIGN: Ambispective observational follow-up study. Patients with focal spasticity secondary to central nervous system injury with elbow flexor pattern who received thermal radiofrequency treatment in the musculocutaneous nerve between 2021 and 2023 were included. SUBJECTS: 12 patients METHODS: Ultrasound-guided thermal radiofrequency was applied to the musculocutaneous nerve at 80º C for 90 seconds. Effectiveness was assessed prior to thermal radiofrequency and at six months using scales to measure pain (VAS), spasticity (MAS), disability (DAS), quality of life (SQol-6D), patient-perceived and physician-perceived satisfaction (PIG-C, PGA), and goal attainment (GAS). Elbow joint range of motion was evaluated via goniometry. Safety was evaluated by assessing side effects. RESULTS: Patients had statistically significant improvements in spasticity (p=0.003), severe elbow flexion (p=0.02), pain (p=0.046), functioning (p<0.05), and spasticity-related quality of life (p<0.05 in three sections). Furthermore, treatment goals were attained. Patient- and physician-perceived clinical improvement was achieved. Regarding side effects, two patients had dysesthesia that was self-limiting, with maximum duration of one month. CONCLUSIONS: Thermal radiofrequency in the musculocutaneous nerve can be a safe, effective treatment for patients with severe spasticity with an elbow flexor pattern.